Epi: An open humanoid platform for developmental robotics. (24th March 2020) - Johansson, Birger; Tjøstheim, Trond A; Balkenius, Christian
Epi is a humanoid robot developed by Lund University Cognitive Science Robotics Group. It was designed to be used in experiments in developmental robotics and has proportions to give a childlike impression while still being decidedly robotic. The robot head has two degrees of freedom in the neck and each eye can independently move laterally. There is a camera in each eye to make stereovision possible. The arms are designed to resemble those of a human. Each arm has five degrees of freedom, three in the shoulder, one in the elbow and one in the wrist. The hands have four movable fingers and a stationary thumb. A force distribution mechanism inside the hand connect a single servo to the movable fingers and makes sure the hand closes around an object regardless of its shape. The rigid parts of the hands are 3D printed in PLA and HIPS while the flexible parts, including the joints and the tendons, are made from polyurethane rubber. The control system for Epi is based on neurophysiological data and is implemented using the Ikaros system. Most of the sensory and motor processing is done at 40 Hz to allow smooth movements. The irises of the eyes can change colour and the pupils can dilate and contract. There is also a grid of LEDs that resembles a mouth that can be animated by changing colour and intensity.